Research of Possibility of Sludge Complex Recycling in Low Radioactive LRW Storage Pools; Advanced Materials Research : Radiation and nuclear techniques in material science; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Karengin A. G. Aleksandr Grigorievich; Tundeshev N. V. Nikolay Vladislavovich; Novoselov I. Yu. Ivan Yurievich; Oreshkin E. A. Egor Aleksandrovich (Nuclear Engineering and Fuel Cycles, 2015)
Title screen